New trends and advancements in metal machining simulation - Vaz Jr. M.* (2007)
Metal cutting modelling and simulation has advanced significantly in the last decade. New models and simulation strategies have been proposed so that a wide range of numerical and physical aspects have been addressed. Despite the recent achievements, some important issues remain open and so far no widespread agreement was reached in a number of them. This paper presents a critical appraisal of some modelling strategies and discusses future trends on simulation of metal machining. © CIMNE, 2007.